Climate variability along latitudinal and longitudinal transects in East Antarctica - Magand O.; Frezzotti M.; Pourchet M.; STENNI, Barbara; Genoni L.; Fily M. (2004)
In the framework of the International Trans-Antarctic Scientific Expedition (ITASE) programme, France and Italy carried out a traverse along one west–east and two north–south transects in East Antarctica from November 2001 to January 2002. Eighteen shallow snow–firn cores were drilled, and surface snow samples were collected every 5km along the traverse. Firn temperatures were measured in boreholes down to 30 m. The cores were analyzed for beta radioactivity to obtain snow accumulation-rate data. The surface snow samples were analyzed for d18O to correlate isotopic values with borehole temperatures. Multiple regression analysis shows a global near-dry-adiabatic lapse rate and a latitudinal lapse rate of 1.05 ̊C ( ̊ lat. S)–1, in the Dome C drainage area. Analysis of firn temperatures reveals a super-adiabatic lapse rate along the ice divide between Talos Dome and the Southern Ocean coast, and in some sectors along the ice divide between the Astrolabe Basin and D59. Snow accumulation rates and firn temperatures show warmer temperatures and higher accumulation values close to the ice divides extending from Talos Dome and Dome C to the Southern Ocean. The spatial pattern of data is linked with a katabatic-wind-source basin and moisture-source region.